Longevidade, efetividade, segurança e impacto na qualidade de vida relacionada à saúde bucal das técnicas de clareamento dentário caseiro e de consultório com peróxidos de baixa concentração: ensaio clínico randomizado - Nayara Kelly Lyrio Ferraz (2018)
Longevity, effectiveness, safety and and impact on oral health-related quality of life of at-home and in-office dental bleaching with low concentration peroxides: a randomized clinical trial The objective of this study was to evaluate the longevity, effectiveness, safety and impact on oral health related quality of life of teeth whitening techniques using low concentrations of peroxides. A randomized, parallel and single blind trial was conducted. The 81 participants were separated into three groups (n = 27): CP10% = Homemade / 10% carbamide peroxide (2 hours per day for 21 days); HP6% = Office / Hydrogen peroxide 6% (30 min / session, 3 sessions, LED / Laser light activation); HP15% = Office / 15% hydrogen peroxide (30 min / session, 3 sessions, LED / Laser light activation). The color of the teeth was evaluated in 5 different moments: T1 (Baseline) = Before treatment; T2 = 1 week after initiation of treatment; T3 = 2 weeks after initiation of treatment; T4 = 1 week after the end of the treatment and T5 = 6 months after the end of treatment, using the Vita Classical color scale and Vita Easy Shade Advance spectrophotometer. Dental sensitivity was assessed using the Numerical Visual Scale and gingival irritation using the Modified Gingival Index - IGM. Oral Impact on Daily Performance (OIDP) was used to assess the impact of bleaching on quality of life. Data were analyzed by the Friedman, Mann-Whitney, Pearson's and McNemar's Chi-square tests (p <0.05). The results were distributed in 2 articles, according to the comparisons of groups CP10% and HP6% in the first article, and HP6% and HP15% in the second article. In the first article, there was a statistically significant difference in color change (E) from T1 to T4 in CP10% (p <0.001) and HP6% (p <0.001). A significant difference of E in T4 was observed between CP10% (9.28) and HP6% (4.47) (p = 0.042). Dental sensitivity was significantly higher (p = 0.008) in CP10% (median = 1.5) than in HP6% (median = 0.0), in T2. Gingival irritation differed significantly (p = 0.002) between CP10% (median = 0.2) and HP6% (median = 0.0) in T2. In the second article no significant differences were observed in relation to the L *, a * or b * parameters, between HP6% and HP15% of T1 to T5. No significant differences were observed between HP6% and HP15% groups in tooth sensitivity or gingival irritation. All the protocols used showed bleaching effectiveness. The office technique with HP6% and HP15% caused low frequency of negative effects such as sensitivity and gingival irritation. In both articles there were no differences of the groups regarding the impact on quality of life related to oral health. In article one, the greater presence of negative effects in the homemade technique did not significantly affect the quality of life related to oral health. Keywords: Dental bleaching. Quality of life. Hydrogen peroxide.